2016
DOI: 10.1186/s40360-016-0071-z
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilization, prescription errors and potential drug-drug interactions: an experience in rural Sri Lanka

Abstract: BackgroundPrescription writing is a process which transfers the therapeutic message from the prescriber to the patient through the pharmacist. Prescribing errors, drug duplication and potential drug-drug interactions (pDDI) in prescriptions lead to medication error. Assessment of the above was made in prescriptions dispensed at State Pharmaceutical Corporation (SPC), Anuradhapura, Sri Lanka.MethodsA cross sectional study was conducted. Drugs were classified according to the WHO anatomical, therapeutic chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 20 publications
3
19
2
Order By: Relevance
“…We found that drug class duplication was seen to be present in 17.68% prescriptions. This is comparable to the results in the study by Rathish et al who found 14.65% of prescriptions containing drug class duplication [7]. One or more FDCs were prescribed in 46.27% prescriptions in our study, while the overall percentage of FDCs from the total number of drugs was 17.36%.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We found that drug class duplication was seen to be present in 17.68% prescriptions. This is comparable to the results in the study by Rathish et al who found 14.65% of prescriptions containing drug class duplication [7]. One or more FDCs were prescribed in 46.27% prescriptions in our study, while the overall percentage of FDCs from the total number of drugs was 17.36%.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, 67.66% of prescriptions were found to be clearly legible. In studies conducted by Saini et al and Rathish et al, the percentage of legible prescriptions was found to be 66% and 26%, respectively, showing wide variability [6,7]. In our study, 43.85% prescriptions diagnosis was not mentioned, while chief complaints were not mentioned in 51.83% prescriptions.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Studies on potential drug-drug interaction (PDDI) in a number of countries reported varying findings. Studies from India and Sri Lanka, which employed Medscape Interaction Checker, reported PDDIs proportions of 83.42% and 52.5% [ 7 , 8 ]. Findings from Brazil and Italy, using Drug Reax of Micromedex, identified 49.7% and 45.3% pairs of medicines with PDDIs [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies in Sri Lanka reporting on prescription errors and medication errors (15,18,19,20,21) but only a few on dispensing errors, their types and prevalence. The study by Hettihewa et al, 2011 (22) reported a low dispenser-patient ratio and the need for introducing a well-prepared medicine labeling system but they did not look for all types of dispensing errors.…”
Section: Introductionmentioning
confidence: 99%